If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+3m=-6m-4(m-4)
We move all terms to the left:
3+3m-(-6m-4(m-4))=0
We calculate terms in parentheses: -(-6m-4(m-4)), so:We get rid of parentheses
-6m-4(m-4)
We multiply parentheses
-6m-4m+16
We add all the numbers together, and all the variables
-10m+16
Back to the equation:
-(-10m+16)
3m+10m-16+3=0
We add all the numbers together, and all the variables
13m-13=0
We move all terms containing m to the left, all other terms to the right
13m=13
m=13/13
m=1
| t^2=6t-4 | | 5n-29=7 | | v-1=-5(3-3v) | | 5/3+y=5/3 | | 7=5n-29 | | 15-a=3(a-3) | | H=-3^2t+6t= | | H=-3t^+6t | | -5(x+3)+2=-21-3x | | 4/5r=12/25 | | C^2-c-12=0 | | 5/x-2=15/x | | 16/9=4y | | 78(−32−48x)+36=23(−33x−18)−10x= | | 12x+6x+5+4x=-10x+5 | | 1-x=6×+1 | | 1/2x+140=120 | | 2(x÷8)=22 | | 9X2+36x-35=0 | | 150-3.50x=130-3x | | 3w+w=72 | | 4(2x+4)=11x-3x+5 | | 5r-25=75 | | -3(m+3)-6m=-4(1+m) | | ⁵⁄₉(y+3)=40 | | 2x+81=180 | | −5(4x−2)+2x+1=−151 | | n-1=n-2 | | -14+41=-3(x+4) | | (3p+1)=0 | | 4.2x4.2=x | | 13x-13=10x-13 |